7+3(2w-1)=-2(8w-9)+6w

Simple and best practice solution for 7+3(2w-1)=-2(8w-9)+6w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(2w-1)=-2(8w-9)+6w equation:


Simplifying
7 + 3(2w + -1) = -2(8w + -9) + 6w

Reorder the terms:
7 + 3(-1 + 2w) = -2(8w + -9) + 6w
7 + (-1 * 3 + 2w * 3) = -2(8w + -9) + 6w
7 + (-3 + 6w) = -2(8w + -9) + 6w

Combine like terms: 7 + -3 = 4
4 + 6w = -2(8w + -9) + 6w

Reorder the terms:
4 + 6w = -2(-9 + 8w) + 6w
4 + 6w = (-9 * -2 + 8w * -2) + 6w
4 + 6w = (18 + -16w) + 6w

Combine like terms: -16w + 6w = -10w
4 + 6w = 18 + -10w

Solving
4 + 6w = 18 + -10w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '10w' to each side of the equation.
4 + 6w + 10w = 18 + -10w + 10w

Combine like terms: 6w + 10w = 16w
4 + 16w = 18 + -10w + 10w

Combine like terms: -10w + 10w = 0
4 + 16w = 18 + 0
4 + 16w = 18

Add '-4' to each side of the equation.
4 + -4 + 16w = 18 + -4

Combine like terms: 4 + -4 = 0
0 + 16w = 18 + -4
16w = 18 + -4

Combine like terms: 18 + -4 = 14
16w = 14

Divide each side by '16'.
w = 0.875

Simplifying
w = 0.875

See similar equations:

| 12r+15=155-2r | | 3c-5=14c-27 | | 50-n=35 | | x^2-3x+438=0 | | 10v+14=80-v | | 6(x+4)=2 | | -6(-4u+2)-6u=2(u-5)-6 | | 2+3(x+2)=5 | | 1.8=vi+1.5(2.5) | | 7-x/11=0 | | n+2=31 | | 6n+4=6 | | 4y-5+5=24 | | x=23/-9 | | 3(v+6)=-3(6v-7)+6v | | 6x-8+5=13x-4+9 | | 24+.16n=40 | | -11v-10v+14v-14v=14 | | 7n-13=13n-15 | | 2Ln(x)+Ln(x-1)=Ln(-2x^2+5x-3) | | -4w-4(5x-5w)+3x= | | X^2-32x+225=0 | | y=50x+1.50 | | 2u-2+2(4u+2)=-2(u+6) | | 15x+-11x+-7x=18 | | 3r-18=2r-12 | | -3a-1=7a | | 6timesd+136=400 | | 1ab+2bc-7ac=10 | | -2x+34=x+16 | | -3(t+5)=-36 | | 12(23x+46y)+23=762 |

Equations solver categories